Dinamizar textos - Carrillo Mateo, Evaristo; González Darder, Javier González; Motos Teruel, Tomás; Tejedo Torrent, Francisco (Biblioteca de Recursos Didácticos Alhambra, 1987)
Sonorizar-- Dramatizar-- Modificar-- Propuestas para modificar textos-- Ilustrar-- Sesiones de trabajo